Driving Socialpreneurship and Diving into Digital Transformation to Enhance Donation Intentions in Indonesia - Sendjaja, Theodorus; Rachbini, Didik J.; Astini, Rina; Asih, Daru (Pandawan, 2025)
This study investigates how digital transformation within the Catholic Church in Indonesia can enhance digital donation intentions by analyzing the influence of trust, Perceived Ease of Use, Perceived Usefulness, perceived risk, and perceived security on attitudes and engagement toward technology acceptance. Employing a quantitative design with an explanatory and cross-sectional approach, data were gathered from 100 respondents across 10 archdioceses in Indonesia using stratified random sampling. The analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships between the variables. The findings reveal significant effects of Perceived Usefulness, Perceived Ease of Use, perceived risk, attitude, and engagement on digital donation intention. These results offer practical insights into improving donation practices and accelerating digital transformation within the Catholic Church in Indonesia. This study further proposes a novel conceptual framework that integrates trust, Perceived Ease of Use, Perceived Usefulness, perceived risk, and perceived security to explain attitudes and engagement in digital donations. This model expands the Technology Acceptance Model (TAM) by incorporating additional factors relevant to donation behavior. Moreover, the study addresses a gap in the literature by highlighting the decline in QRIS adoption following the COVID-19 pandemic-an issue rarely discussed in prior donation studies. Digital donations in this context are also positioned as part of a broader social entrepreneurship movement that leverages technology to foster community involvement and ensure the financial sustainability of religious institutions.